KIR haplotypes defined by segregation analysis in 59 Centre d’Etude Polymorphisme Humain (CEPH) families - Martin, M. P. (2008)
The killer cell immunoglobulin-like receptor (KIR) gene cluster exhibits extensive allelic and haplotypic diversity. Variation at the locus is associated with an increasing number of human diseases, reminiscent of the HLA loci. Characterization of diversity at the KIR locus has progressed over the past several years, particularly since the sequence of entire KIR haplotypes have become available. To determine the extent of KIR haplotypic variability among individuals of northern European descent, we genotyped 59 CEPH families for presence/absence of all KIR genes and performed limited allelic subtyping at several KIR loci. A total of 20 unique haplotypes differing in gene content were identified, the most common of which was the previously defined A haplotype (f=0.52). Several unusual haplotypes that probably arose as a consequence of unequal crossing over events were also identified. Linkage disequilibrium (LD) analysis indicated strong negative and positive LD between several pairs of genes, values that may be useful in determining haplotypic structure when family data are not available. These data provide a resource to aid in the interpretation of disease association data involving individuals of European descent.